Delimiting Central Europe as a Juridical Space: A Preliminary Exercise in Critical Legal Geography - Mańko, Rafał (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The aim of the present paper is to contribute to the on-going discussion, both in legal theory and in comparative law, concerning the status of Central Europe and its delimitation from other legal regions in Europe, notably Romano-Germanic Western Europe but also Eastern Europe and Eurasia. The paper adopts the methodological perspective of critical legal geography, understood as a strand of critical jurisprudence laying at the interstices of spatial justice studies, critical geography, comparative law, sociology of law and legal history. The paper proceeds by identifying the notion of Central Europe with reference to a specific list of countries, then proposes a number of objective criteria for delimitng Central Europe and applies them in order to highlight the difference between Central Europe and other adjacent legal regions. Following that, the paper enquires as to whether Central Europe should be deemed to be a ‘legal family’, a ‘legal union’ or simply a ‘legal space’ or ‘space of legal culture’.